Produção da microalga Scenedesmus sp. em manipueira para extração de lipídios - Cerqueira, Keilla Santos (2019)
Microalgae such as Scenedesmus sp. are sources of renewable energy and have been studied for the production of several bioproducts, among which the lipids, which can be applied in the energy and food sector, stand out. The production of lipids through microalgae has some bottlenecks, such as nutrition, form of cultivation and the need to break the cell structure; since lipid is an intracellular product, in addition to the difficulties associated with extraction and purification. In view of this problem related to microalgal nutrition and lipid recovery, the present study aims to analyze some factors that influence the growth of the biomass of the microalga Scenedesmus sp. in a medium supplemented with manure - liquid effluent from the pressing of manioc in the production of flour, is generally discarded in a concentrated way, attacking the environment, it is a nutrient rich effluent and has a high organic load, being able to provide for the microalgae complementation nutritional balance required for the production of lipid-rich biomass with characteristics similar to those of oleaginous plant oils that produce biodiesel - in different concentrations diluted in ASM-1 synthetic medium, thus evaluating cell density, culture conditions, dry biomass and lipid content through the study of cell lysis and extraction forms. Scenedesmus sp. was grown aseptically for 10 days in different photoperiod cycles, different nitrate concentrations and different phosphate concentrations at room temperature. In order to recover lipid, two types of pre-treatments (ultrasonic and autoclave) were used to perform the breakdown of the molecule, two solvent systems (EC-Chloroform / ethanol and CM-Chloroform / methanol) and two extraction methods Bligh and Dyer (1959) with ultrasound and Soxhlet. In this way Scenedesmus sp. (1.3 gL-1) and the highest lipid content (18.28%), using 18h of exposure to light, 39.75 mg.L-1 of phosphates, 85 mg.L-1 of nitrate on the seventh day of culture. It was observed that for both solvent systems, autoclave pretreatment was more efficient; however, the Bligh and Dyer (1959) method adapted with the use of ultrasound and chloroform / ethanol solvent systems obtained a higher yield (19.27%) and low thermal energy cost when compared to Soxhlet with the same solvent system which resulted in 15.71% total lipid extracted. Under these optimized conditions the culture media supplemented with manipueira (5% - 10%) presented better efficiency in the production of dry biomass of microalgae compared to the synthetic culture medium. The analysis of the lipid profile suggests the possibility of using microalgae oil to produce biodiesel due to the low unsaturation content, lower than that of vegetable oils (soybean, cotton and cinnamon).